The Power of Parting Words: Collective Memory in Local Television News Exit Interviews. Issue 1 (2nd January 2021) - Daniels, George L.; Tait, Gabriel B.
ABSTRACT: Media historians study the "dynamic dimension of historical memory." Describing where one has been and influencing where one is going, historical memory serves as a snapshot to capture a moment or set of moments that can be frozen in time. This article provides an understanding of the historical and collective memory of eighteen employees who left their television news jobs after decades at a single local station. Eight of the broadcast journalists were given buyouts as part of downsizing at WXIA-TV, the NBC affiliate in Atlanta, Georgia that is part of TEGNA. But, departing employees at two other stations in Atlanta and seven other markets also left messages worthy of closer analysis of their most poignant memories. The findings reveal how collective memory is processual, unpredictable, partial, usable, both particular and universal, and material. These six categories reveal the "Power of Parting Words" in "exit interviews" and the significance historical memory has in an institutional context of journalism. Since leaving their jobs in 2016, two of the employees in this research have passed away. Their archived interviews are central elements of "memorializing discourse" scholarship and convey a component of collective memory that invokes shared norms and values.